EKSISTENSI PENDIDIKAN ISLAM DI ABAD PENGETAHUAN - Tohir Tamimi, Muhyiddin (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2009)
This article would like to explore about expectation and opportunity of Islamic education for Muslim society (ummah). The method of this topic is descriptive and analyse. Explanation dividied in five division: Introduction, definition of education, expectation of Muslim society, opportunity and conclusion. In the age of science existension of Islamic education is very urgent and very important especially for the ummah because Islamic education is to perfect and actualize all the possibilities of the human soul leading finally to that supreme knowledge of the Divinity which is the goal of human life. While education prepares man for felicity in this life, its ultimate goal is the abode of permanence and all education points to the permanent world of eternity (al-akhirah) beyond the transient vacillations of this world of change. This article also analyse on the problem of Islamic education such as bad of management and administration, low facility and quality of teacher, and degradation of moral. In the age of science and information society, hight quality of education is something necessary for renaissance of Muslim society